2017
DOI: 10.29356/jmcs.v57i3.211
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies and DFT Calculations of Cimetidine Complexes with Transition Metal Ions

Abstract: The coordination behavior of the antiulcer drug cimetidine (cime) towards transition metal ions was investigated. The synthesis and characterization of [Cr(cime)<sub>2</sub>Cl<sub>2</sub>]Cl·3H<sub>2</sub>O, [Co(cime)Cl<sub>2</sub>]·5H<sub>2</sub>O, [Co(cime)<sub>3</sub>Cl]Cl·3H<sub>2</sub>O, [Ni(cime)Cl<sub>2</sub>(H<sub>2</sub>O)<sub>2</sub>]·H<sub>2</sub>O, [Cu(cime)Cl<sub&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The electronic spectra of the Co(II) complex displays two bands at 10150 cm -1 (n 1 ) and 22125 cm -1 (n 3 ), which are assigned to 4 T 1g (F)→ 4 T 2g (F)(n 1 ); 4 T 1g (F)→ 4 T 1g (P)(n 3 ) transitions, respectively. These are the characteristic bands of high spin octahedral Co(II) complexes 20 .…”
Section: Uv-vis Spectra and Magnetic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic spectra of the Co(II) complex displays two bands at 10150 cm -1 (n 1 ) and 22125 cm -1 (n 3 ), which are assigned to 4 T 1g (F)→ 4 T 2g (F)(n 1 ); 4 T 1g (F)→ 4 T 1g (P)(n 3 ) transitions, respectively. These are the characteristic bands of high spin octahedral Co(II) complexes 20 .…”
Section: Uv-vis Spectra and Magnetic Measurementsmentioning
confidence: 99%
“…and also for their simple methods to be prepared. Many studies reported several metal complexes of Schiff base derived from different antibiotics and their biological activity [1][2][3][4][5][6][7][8] . In all these cases it was found that metal complexes showed increased antimicrobial activity than their parent Schiff bases.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic absorption spectroscopy transition metal complexes can bind to DNA through covalent bonding via replacement of a labile ligand of the complex by a nitrogen base of DNA such as guanine N 7 or non-covalent interactions such as intercalation, electrostatic, or groove binding 25 . Electronic absorption spectroscopy is one of the most useful techniques in DNA binding studies since the observed changes in the spectra may give indication of the mode of interaction.…”
Section: Dna Binding -Electronic Absorption Studymentioning
confidence: 99%
“…It was found through electrostatic potential maps that the more reactive zones of CimA are in the imidazolic nitrogen and the thioether sulfur. 19 Additionally, Singh et al found, at the B3LYP/6-31G*(d,p) level, that cimetidine is able to donate electrons through nitrogen and oxygen atoms to an acceptor molecule with empty and low energy orbital. 20 However, in spite of the interest dedicated to cimetidine from experimental and theoretical point of views, the chemical reactivity of cimetidine A, C and D at the molecular level in different solvents have not hitherto been analyzed.…”
Section: Introductionmentioning
confidence: 99%